2019
DOI: 10.1108/pijpsm-06-2019-0081
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the police code of silence

Abstract: Purpose The purpose of this paper is to explore the contours of the police code of silence, a critical component of the ability to control misconduct and enhance integrity within any police agency. Unlike the extant research, dominated by single-country studies, this paper provides an in-depth exploration of the code across five countries and tests the relation between the code of science and societal characteristics. Design/methodology/approach A police integrity survey was used to measure the contours of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…, 2016a). It is worth noting that, overall, the predicting power of these demographic factors for the code of silence seems to be lower than that of factors at the organizational or environmental level (Kutnjak Ivković, 2012; Kutnjak Ivković et al. , 2019).…”
Section: Factors Influencing the Code Of Silence: A Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…, 2016a). It is worth noting that, overall, the predicting power of these demographic factors for the code of silence seems to be lower than that of factors at the organizational or environmental level (Kutnjak Ivković, 2012; Kutnjak Ivković et al. , 2019).…”
Section: Factors Influencing the Code Of Silence: A Literature Reviewmentioning
confidence: 95%
“…Moreover, studies have generally revealed that officers' years of experience were negatively associated with police misconduct and the code of silence (see Kutnjak Ivkovi c et al, 2016a). It is worth noting that, overall, the predicting power of these demographic factors for the code of silence seems to be lower than that of factors at the organizational or environmental level (Kutnjak Ivkovi c, 2012;Kutnjak Ivkovi c et al, 2019).…”
Section: Predicting the Police Code Of Silence 71mentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research into police attitudes to sexual misconduct has described this as part of the ‘blue wall of silence’ (Kutnjak Ivković et al, 2019; Maher, 2003). This wall is reportedly strengthened by collegial loyalty, organisational resistance in encouraging reporting and supervisors turning a blind eye (Lee et al, 2013).…”
Section: Barriers To Reportingmentioning
confidence: 99%
“…Mollen (1994) also describes the major obstacle to controlling misconduct in the workplace as a code of silence. Numerous scholars have argued that the code of silence is a key element of police occupational subculture, with veteran officers socializing junior colleagues to express loyalty to their peers by engaging in and upholding the expected silence (Branko et al, 2016;Kutnjak Ivkovic ́et al, 2016b, 2019Louise and Tim, 2016). As a reward for keeping silent about their peers' misconduct, police gain the faith of their fellow officers and expect to obtain reciprocal protection when needed (Kutnjak Ivkovic ́et al, 2019).…”
Section: Introductionmentioning
confidence: 99%